Analysis of The Relationship Between Lifestyle and The Incidence of Dyspepsia in The Working Area of UPTD Oebobo Community Health Center, Kupang City, 2023.: Analisis Hubungan Gaya Hidup Terhadap Kejadian Penyakit Dispepsia di Wilayah Kerja UPTD Puskesmas Oebobo Kota Kupang 2023 - Pellondou, Deflin; Tira, Deviarbi Sakke; Riwu, Yuliana Radja; Tedju Hinga, Indriati A. (Universitas Mohammad Husni Thamrin, 2025)
Background: Dyspepsia is a syndrome or collection of symptoms, where patients experience complaints in the form of pain or discomfort in the epigastrium, nausea, vomiting, bloating, satiety, fullness, belching, bloating and a burning sensation that spreads to the chest. Objective: This study aims to analyze the relationship between lifestyle and the incidence of dyspepsia in the UPTD Oebobo Health Center Work Area in 2023. Method: This study is an analytical observational study using a Case Control design. This research was conducted at the UPTD Oebobo Health Center in May-June 2024. The population in this study were all residents/communities who visited the UPTD Oebobo Health Center as many as 18,105 people. The sample in this study was 118 respondents with a ratio of 1: 1, namely 59 respondents from the case group and 59 respondents from the control group, data collection was carried out using interview techniques to 118 respondents using random sampling techniques. Results: The results of the study showed that diet (p = 0.000; OR = 11.926), alcohol consumption habits (p = 0.043; OR = 2.127), stress (p = 0.001; OR = 5.538) had a significant relationship with the incidence of dyspepsia. Smoking behavior (p = 0.134; OR = 1.761) did not have a significant relationship with the incidence of dyspepsia. Conclusion: diet, alcohol consumption habits and stress have a significant relationship with the incidence of dyspepsia in respondents, while smoking behavior does not have a significant relationship with the incidence of dyspepsia in respondents. Therefore, to prevent the occurrence of dyspepsia, people can adopt a healthy lifestyle such as diligently checking their health, implementing a good diet such as choosing the types of food and drinks to be consumed, setting daily meal times and frequencies, and how to control stress so that people can avoid the occurrence of dyspepsia.